Assessing Visual Spatial Intelligence on Biology Content - Baiq Fatmawati*; Nuryani Y. Rustaman; Purwati Kuswarini Suprapto (Jurnal Pendidikan Sains Indonesia, 2021)
One of the assessments in the learning processes is assessment of skills, the drawing is one of the competancy components standard of graduation in 2013 curriculum. However, teachers rarely do this assessment during the learning process instead microscopic practicum on abstract material including biology subjects. The research aim is to assess students' spatial visual intelligence on plant cell material and plant tissues, find out understanding concepts and student responses to apply spatial visual learning. The participants were 20 students SMA NW Pancor. Data collection used was students’ worksheets, and questionnaires. The data analysis was qualitative descriptive. The findings, spatial visual intelligence was seen when the teacher asked students to draw 2D cells and plant tissues before began to the core material, but did not appropriate with its’ original design. There are differences in the acquisition of scores on plant cell and tissue material, this proves that to help students' memory in making 2D images and understanding concepts, contextual media is needed such as by showing real objects and or it can also be done practicum. Therefore, the teacher can identify early about assessing the spatial visual competence, it was done by looking at the similarity of images made to the original, from the images made can be seen the students’ concepts mastery of the material being taught.